Governance Competence in the Implementation of Independent Mosques in Medan Selayang District - Haikal, Muhammad Fachran; Kurniawan, Rhohis; Zihad, Aidil (Jurnal Ilmiah Sumber Daya Manusia, 2025)
The importance of competence in mosque management with management units carrying out management in terms of aspects of idarah, imarah and riayah, this is able to maintain optimal performance, to create an independent mosque. The aim of this research is to determine the influence of the competency dimensions of knowledge, skills and attitudes of mosque managers on the implementation of Independent Mosques in Medan Selayang District, both partially and simultaneously. The research method used is quantitative descriptive and verification carried out through data collection in the field. The analytical method used in this research is a quantitative method. Questionnaire data collection techniques, observation and documentation. The data analysis technique was carried out using multiple linear regression analysis with the hyopthesis test, t test, f test and determination test. Research result Simultaneous and partial testing found an influence on knowledge, skills and attitudes towards the implementation of the Mandiri mosque in Medan Selayang District.